Penguatan Kapasitas Pengetahuan Siswa Smp 3 Simpang Empat Mataraman Kabupaten Terhadap Penyakit Kardiovaskular - hammad, hammad; Sajidah, Ainun; Rasyid, Muhammad; Rahman, Arief 4; Rahmana, Muhamad Syeikha; Kaila, Wafa (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Cardiovascular diseases caused by high cholesterol levels have become a significant health issue in Indonesia, including in the Banjar Regency area. The low level of public understanding, particularly in riverbank communities, regarding the dangers of high cholesterol and its prevention methods, can increase the risk of cardiovascular disease occurrence. This community service program aims to strengthen the capacity of school students in the riverbank areas of Banjar Regency to recognize and prevent the risks of cardiovascular diseases caused by cholesterol. The methods used in this program include providing education through interactive lectures and simulations, as well as guidance related to cholesterol checks by the Banjarmasin Health Polytechnic team to students of SMPN 3 Simpang Empat. The results of the program show an increase in students' knowledge and awareness of cholesterol risk factors and preventive measures. It is suggested that through this program, students can become agents of change in their families and communities by adopting a healthy lifestyle to reduce the risk of cardiovascular disease in the future.